The Role of the Dikyasa Unit through the Traffic Dikmas in Preventing Traffic Accidents in the Legal Territory of the Bogor Resort Police - Evander Parulain (Police Studies Review, 2021)
This research is motivated by the high number of accidents that occur from year to year in the jurisdiction of the Bogor Police. Judging from the last 5 years the number of accidents at the Bogor Police has always increased. However, there was a significant decline in 2020, this was influenced by the Covid-19 pandemic. The important role of the Bogor Police Traffic Unit, especially the Dikyasa Unit, is in preventing accidents, which are carried out through public education activities in the traffic sector. Therefore, a research was conducted on the role of the Dikyasa Unit through the Dikmas and in preventing traffic accidents in the jurisdiction of the Bogor Police, as well as the factors that influence the role of the Dikyasa Unit. This research was carried out with a qualitative approach that focused on the implementation of community education services in the jurisdiction of the Bogor Police. Data collection techniques are interviews, observations, and documentation studies. Data validity was carried out using source triangulation and technical triangulation. Data analysis techniques used in the form of data reduction, data presentation, and drawing conclusions. The results of the study found that the Dikyasa Unit through Dikmas then in preventing traffic accidents in the jurisdiction of the Bogor Police which was analyzed using Management Theory, Communication Theory, Juklak Kapolri No.Pol: JUKLAK/5/V/2003, Law No. 22 of 2009, has not played a role in prevent traffic accidents. The implementation of community education has not met the standard indicators in past social education activities. Based on the results of the study, the researchers suggest making technology-based social education activities such as webinars that can facilitate the implementation of community education, especially during the Covid-19 pandemic.